Comparative Role of Anti-TNF Agents versus IL-12/23 Inhibitors in Inflammatory Bowel Disease: An Updated Review - Leong, Xue Bin; Tang, Chuan Zhe; Lee, Chloe Zi Ying; Lee, Zoe Ling Hui; Koo, Thai Hau (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Treatments for Crohn's Disease (CD) and Ulcerative Colitis (UC), two conditions that fall under the umbrella of Inflammatory Bowel Disease (IBD), must be both safe and effective. This review compares the effectiveness and safety of anti-TNF agents and IL-12/23 inhibitors, specifically in the context of IBD management. Randomized controlled trials (RCTs), observational studies, and meta-analyses involving adult IBD patients were all included in the review. Anti-TNF agents (infliximab and adalimumab) were shown to significantly improve clinical remission rates and reduce complications, particularly with early intervention. However, these agents were associated with adverse effects such as infections and autoimmune reactions. IL-12/23 inhibitors, particularly risankizumab, showed superior efficacy in achieving and maintaining remission with a better safety profile. The findings prove that IL-12/23 inhibitors might be more effective for patients who are unresponsive to anti-TNF therapies. In conclusion, both anti-TNF agents and IL-12/23 inhibitors effectively manage IBD, with IL-12/23 inhibitors offering a favorable safety profile. Early intervention and personalized treatment strategies are significant for optimizing patient outcomes. It will take additional research to validate these results and improve treatment strategies.